Implementasi Model Pembelajaran STAD Berbantuan Media Kartu Soal dengan Konteks Madiun Kota Pendekar untuk Meningkatkan Motivasi Belajar Matematika Peserta Didik - Rizky Andriyanto; Wasilatul Murtafiah; Henri Yuli Hartanto (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
This research is classroom action research that aims to determine students motivation of mathematics learning. This research uses the Student Teams Achievement Division (STAD) learning model with question cards in the Madiun context of the Warriors City, that carried out in two cycles using the Kemmis & McTaggart stages. Subjects of this research were 32 students in class VII C at SMPN 4 Madiun for the 2023/2024 academic year. The data obtained in this study through a student learning motivation questionnaire was analyzed in the form of percentages. The results of the research were obtained showed that the learning motivation of class VII C students in the pre-cycle was 48.52%, cycle 1 was 69.01%, and cycle 2 was 84.42%. Based on the research results, it can be concluded that the use of the STAD learning model with question cards in the Madiun context of the Warriors City can increase the learning motivation of class VII C students at SMPN 4 Madiun towards mathematics learning.